Economic Analysis of Induction versus Elective Cesarean in Term Nulliparas with Supermorbid Obesity - Nehme, Lea; Horgan, Rebecca; Waller, Jerri; Kumar, Priyanka; Barake, Carole; Huang, Jim C.; Saade, George; Kawakita, Tetsuya (American Journal of Perinatology, 2023)
Objective We sought to evaluate the economic benefit of the induction of labor compared with elective cesarean delivery in individuals with supermorbid obesity (body mass index 60 kg/m2 or greater) at term.Study Design We developed an economic analysis model to compare induction of labor with elective cesarean delivery in nulliparous individuals with supermorbid obesity at term. The primary outcome was the total cost per strategy from a health system perspective with elective cesarean delivery as a reference group. Pregnancy outcomes for the index and subsequent pregnancies were considered. When available, probabilities of pregnancy outcomes were extracted from our institutions. Rare pregnancy outcomes, relative risks, and costs were derived from the literature. All costs in this analysis were inflated to 2022 USD (U.S. dollar). To determine the robustness of the decision model, we conducted one-way sensitivity analyses by changing point estimates of variables. We then performed a probabilistic sensitivity analysis using Monte Carlo simulation repeating 1,000 times to test the robustness of the results in the setting of simultaneous changes in probabilities, relative risks, and costs.Results In the base-case analysis, assuming that 72.7% of nulliparous individuals undergoing induction of labor would have a cesarean delivery, induction of labor would cost $41,084 compared with $40,742 for elective cesarean delivery, resulting in a higher cost of $342 per nulliparous individuals with supermorbid obesity. In a sensitivity analysis, we found that induction of labor compared with elective cesarean is less economical if the probability of cesarean delivery after induction of labor exceeds 71%. Monte Carlo simulation suggests that elective cesarean delivery was the preferred cost-beneficial strategy with a frequency of 53.5%.Conclusion: Among our patient population, induction of labor was less economical compared with elective cesarean delivery at term for nulliparous individuals with supermorbid obesity.Key Points
Keywords: obesity; induction of labor; cesarean delivery; economic analysis